PENERAPAN MODEL SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 16 PIDIE - Syarifah Rahmi (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to determine the process of improving student learning outcomes through the scramble learning model in 4th grade students. The research design used is the type of Classroom Action Research (CAR) with the Kemmis and Mc. Tanggart model. The subjects in this study were 8 of 4th grade students consisting of 5 females and 3 males. Data collection in the study was carried out through observation, tests, and documentation. The application of the scramble model began with the distribution of question cards and answer cards. The results of the student learning research in cycle I obtained 25% of students who completed learning with an average score of 55. In cycle II it became 65.50% with an average score of 73.13, and increased in cycle III to 87.50% with an average score of 81.87. It can be concluded that the application of the scramble learning model can improve the learning outcomes of 4th grade